ANALISIS STRATEGI PENINGKATAN PRESTASI KERJA KARYAWAN MELALUI KOMPETENSI DAN KOMITMENT ORGANISASIONAL DALAM PERSPEKTIF PERBANKAN SYARIAH (Study Kasus Pada PT. Bank BTN (Persero),Tbk) - Widawati, Fera; Supriyadi, Edy; Purwoko, Bambang (SEKOLAH PASCASARJANA PRESS, 2017)
Increasing complexity of business competition and achievement of company performance demands are high demanding role of human resource management. Request a workforce with the skills, knowledge, and skill also increases. Changes in the business environment that occurs leads to the recognition of the importance of human resources as a source of competitive advantage for the Organization, the employee competencies that correspond to the needs of the companies can give impact on the commitment of the employees to achieve the vision and mission of the company is ultimately reflected on the employee's achievements and performance of the company. This research uses three variables, namely competency, organizational commitment, and work achievement. The purpose of this research is to analyze the strategy of increasing employee achievement through organizational commitment and competence as well as composing the SWOT analysis in an effort to the preparation of the strategic plan with regard to the performance of the employee. The research method used was qualitative and quantitative methods. Data processing used in Structural Equation Modelling (SEM). Methods of sampling, cluster sampling is used with the sample number of 245 people. The respondents in this study i.e. all employees in four offices, namely BTN BTN Sharia branch Sunday market, BTN Sharia Branch Office Bogor, BTN Sharia Branch Office Tangerang and Bekasi Branch Office Sharia BTN. Hope the findings of this research is the competence and commitment of organizational impact significantly to achievements of employees and interns based on the SWOT analysis can be formulated strategies to improve employees work achievement with maximize the strengths and minimize the weaknesses and the opportunities and threats so that can becomes a formula for sustainable human resource development that can support the achievement of company performance and have appropriate work achievements with expectations of the company.